MAKSUD PESERTA TUTUR DALAM KONTEKS JAWABAN ANAK-ANAK HAKUNLAH URANG PADA KELUARGA BANJAR - Rissari Yayuk (Balai Bahasa Kalimatan Selatan, 2019)
The problems discussed in this study are as follows. 1) What do speakers mean in the context of children's answers to hakunlah urang in the Banjar family? 2) What is meant by partners in the context of children's answers to hakunlah urang in the Banjar family? The objectives of this study are as follows: 1) what the speaker meant in the context of children's answers to hakunlah urang in the Banjar family 2) what is meant by partners talking in the context of children's answers to hakunlah urang in the Banjar family. Type of qualitative descriptive research. Data sources were disclosed by the Banjar community in Kampung Tabah, Banjar Regency. The time of data collection is January 2019 until March 2019. The technique of data collection is recording and recording. This research uses three steps of work, namely (1) providing data; (2) data analysis; and (3) presentation of the results of data analysis. The theory used is speech act. Data analysis results. 1). the purpose of the speaker in this title. Asking to buy something. b. asking to get something c. asking to do something immediately. d. forbid something. e. remind something. Meanwhile the purpose of the partners talking a. accept with pleasure b. accept by force. c. reject firmly. The conclusion is that the purpose of the speaker is to make the couple do something, while the couple's intention is to accept, accept by force, and refuse altogether